Pengaruh Employee Stock Option Plan (ESOP) pada Earnings Management dan Leverage Sebagai Variabel Pemoderasi - Bayu Kuta Waringin, Gusti Ngurah; Dewi, Luh Gede Krisna (E-Jurnal Akuntansi; Vol 25 No 1 (2018), 2018)
The purpose of this study was to obtain empirical evidence of leverage ability to moderate the effect of ESOP on earnings management. The population in this study were companies that registered their shares on the Indonesia Stock Exchange in 2012-2016. The sample in this study was taken using purposive sampling technique based on the technique of determining the sample with the consideration that the company has listed its shares and announced the ESOP on the Indonesia Stock Exchange in the period 1 January 2012 to 31 December 2016.. The analysis technique used in this study is by using the Moderated Regression Analysis (MRA) technique. Based on the results of the study shows that leverage weakens the influence of the Employee Stock Option Plan (ESOP) on corporate earnings management. This shows that with the leverage variable, the negative influence of ESOP on earnings management will decrease. Keywords: Employee stock option plan, leverage, earnings management